Color Compensatory Mechanism of Chromatic Adaptation at the Cortical Level. (June 2022) - Shimakura, Hitomi; Sakata, Katsuaki
Reportedly, some chromatic adaptations have extremely short temporal properties, while others have rather long ones. We aimed to dynamically measure the transition of a neutral point as an aftereffect during chromatic adaptation to understand the temporal characteristics of chromatic adaptation. The peripheral retina was exposed to a yellow light to progress color adaptation, while the transition of a neutral point was measured at the fovea. In Experiment 1, the aftereffect had initially progressed but subsequently recovered despite ongoing chromatic adaptation and regardless of the retinal exposure size, suggesting that the adaptation mechanism at the cortical level continues to readjust the color appearance based on daylight conditions. Experiment 2 was similar to Experiment 1, except that it included participants of varying ages. Older eyes behaved in a homologous manner with younger eyes in Experiment 2, albeit quantitative differences. Regardless of age, similar recalibration of neutral points shifted by color adaptation suggests the color compensation function in older eyes may not change due to long-term chromatic adaptation by optical yellowing. In conclusion, the chromatic adaptation mechanism at the cortical level readjusts color perception, even in younger eyes, according to the daylight neutral point. This daylight information may be stored in the neural mechanism of color vision.